Endoscopic Transcanal Autologous Cartilage Ossiculoplasty - Potsangbam, Dhakeswar Singh (Indian J Otolaryngol Head Neck Surg, 2018)
This was a randomized clinical trial, of thirty-two patients undergoing endoscopic ossiculoplasty, as a second look surgery, at 6 months after primary endoscopic cholesteatoma surgery, in a duration of 9 years. All patients underwent trans-canal endoscopic ossiculoplasty under local anesthesia. Prosthesis used were (1) Titanium partial ossicular replacement prosthesis (PORP) in fourteen, (2) Titanium total ossicular replacement prosthesis (TORP) in six and (3) Autologous cartilage in twelve cases. Puretone audiometry (PTA) were done preoperatively and postoperatively at 2 months and 3 years. Out of twenty-four cases, which presented only with stapes superstructure; fourteen underwent PORP ossiculoplasty and twelve had cartilage short columella ossiculoplasty (SCC). Out of eight cases, which had only mobile stapes footplate, six underwent TORP ossiculoplasty and only two underwent long columella cartilage ossiculoplasty (LCC). Pre-operative average air conduction threshold (AC) of pure tone audiometry were 45.47 dB (PORP), 66.10 dB (TORP), 49.15 dB (SCC) and 59.15 dB (LCC) groups. The post-operative AC at 2 months were respectively 27.37 dB (PORP), 45.83 dB (TORP), 29.99 dB (SCC) and 39.15 dB (LCC) groups. The gap of air and bone conduction (ABG) at 2 months post-operative stage were 19.05 dB (PORP), 20 dB (TORP), 20.32 dB (SCC) and 39.15 dB (LCC) groups and not much changed after 3 years. Extrusion occurred in three PORPs and four TORPs at 4–8 years after surgery. Four cases were lost to follow up. No extrusion occurred in cartilage ossiculoplasty. Trans-canal endoscopic autologous cartilage ossiculoplasty shows encouraging results comparable to titanium prosthesis in repairing ossicles in cholesteatoma disease.